EARLY CHILDHOOD EDUCATION: A PERSPECTIVE FROM THE HOLISTIC EDUCATION PARADIGM - Indrawati Noor Kamila (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID) Ciamis Jawa Barat, 2022)
This study aims to investigate the idea of early childhood education from a holistic standpoint. A literature review is the technique employed. Using this approach, the author compiles, organizes, and evaluates the literature on early childhood education from the viewpoint of a holistic educational paradigm. According to this study, the fundamental tenet of holistic education is that children are complete individuals with cognition, affection, psychomotor skills, a soul, and a physical body who can discover their identity, meaning, and purpose in life through their interactions with others, the natural world, and spiritual principles. According to the holistic education paradigm, early childhood is seen as a whole being that is both a subject and an object of education. It is multifaceted, has a natural history, and has both strengths and shortcomings. These terms are pertinent to Islamic education, which aims to fully and fairly develop human potential in accordance with the idea of